The Effect of Emotional Intelligence and PAI Learning on Religious Behavior in SMA Adabiah 1 Padang, Indonesia - Remiswal Remiswal; Mahmud Mahmud; Sudirman Sudirman (DAYAH: Journal of Islamic Education, 2022)
This study aims to determine the effect of emotional intelligence and Islamic religious education learning on the religious behavior of students at SMA Adabiah I Padang. It is a field research (field research) using a quantitative approach and correlational methods with a population of all students in class XI and Class XII with the proportionate stratified random sampling technique, to obtain a sample of 86 students. Data were collected using a questionnaire and documentation and analysis techniques using the analysis requirements test, classical assumption test, and hypothesis testing. The results showed that first, emotional intelligence had a positive and significant influence on the Religious Behavior of Students at SMA Adabiah I Padang. This can be seen based on the value of the regression coefficient (b1) or slope of 0.504, and the value of Fount (28.606) is greater than Ftable (3.94), and the significance value (0.000) is smaller than the value of α = 0.05. While the contribution of Emotional Intelligence (X1) to religious behavior (Y) is 0.254 or 25.4%, secondly, Islamic Religious Education Learning has a positive and significant influence on the Religious Behavior of Students at SMA Adabiah I Padang. This can be seen based on the regression coefficient (b2) or slope of 0.0435, and the value of Fcount (22.293) is greater than Ftable (3.94), and the significance value (0.000) is smaller than the value of α = 0.05. While the contribution of Islamic Religious Education Learning to Religious Behavior is 0.21 or 21%, the three Emotional Intelligence and Learning Islamic Religious Education together (simultaneously) have a positive and significant influence on the Religious Behavior of Students at SMA Adabiah I Padang. This can be seen based on the value of the regression coefficient (b1) or slope of 0.005 and the value of the regression coefficient (b2) or slope of 0.005, and the value of Fcount (24.623) is greater than Ftable (3.09), and the significance value (0.000) is more. smaller than the value α = 0.05. While the contribution of Emotional Intelligence (X1) and Learning Islamic Religious Education (X2) together (simultaneously) to religious behavior (Y) is 0.372 or 37.2%.